Hubungan antara Dukungan Emosional dengan Perilaku Menyakiti Diri (Self-injury) pada Pengguna Media Sosial Twitter - Prasetyo, Maria Putri; Engry, Agustina (Psychopreneur Journal, 2023)
Self-injury is the behavior of intentionally and consciously hurting certain body parts to channel pain emotionally without any desire to die. Emotional support is the support given by an individual to another individual by providing care. The purpose of this study was to examine the relationship between emotional support and self-injury behavior on Twitter users. The sampling technique used is purposive sampling. The self-injury measuring instrument uses the Indonesian translation of the Self-Harm Inventory by Kusumadewi, et al., (2019), while the emotional support measuring instrument is compiled by researchers. This study obtained 224 research subjects, using the Kendall Tau-b correlation test for data analysis. The results of data analysis obtained a correlation value of 0.000 with p ≤0.050, which means that there is a significant relationship between emotional support and self-injury behavior on Twitter users